Preparation method of novel mixed metal oxide coating titanium electrode

Through low-temperature plasma treatment, pulsed bias magnetron sputtering and laser-induced atomic layer deposition technology, the problems of insufficient bonding strength and poor uniformity of mixed metal oxide-coated titanium electrodes were solved, the preparation of high-performance electrodes was achieved, and the stability and electrocatalytic performance of the electrodes were improved.

CN120719264APending Publication Date: 2025-09-30GUANGZHOU RISING DRAGON ELECTRONICS & PLASTICS TECH

Patent Information

Application Number
CN202510873565.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

The existing method for preparing titanium electrodes coated with mixed metal oxides has problems such as easy cracking and falling off of the coating, poor uniformity, high cost, low deposition rate and insufficient bonding strength, which makes it difficult to meet the preparation requirements of high-performance electrodes.

Method used

By combining low-temperature plasma treatment, pulsed bias magnetron sputtering and laser-induced atomic layer deposition (LA-ALD) technology, a highly adhesive, dense and uniform mixed metal oxide coating is formed by treating the titanium substrate surface, magnetron sputtering the bottom layer and laser depositing the modification layer.

Benefits of technology

It significantly improves the bonding strength between the coating and the titanium substrate and the stability of the electrode, enhances the electrocatalytic performance, extends the service life, and adapts to the needs of different electrochemical application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120719264A_ABST
    Figure CN120719264A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a novel mixed metal oxide coating titanium electrode, and relates to the technical field of electrode preparation, the method comprises the following specific steps: titanium substrate pretreatment: a titanium plate is sequentially subjected to gradient polishing with 120-800-mesh abrasive paper, the polished titanium substrate is subjected to hydrochloric acid solution etching, argon plasma surface activation and drying treatment, and a titanium substrate is obtained; obtaining a clean substrate surface with proper roughness; through the low-temperature plasma treatment, pulsed bias magnetron sputtering and laser-induced atomic layer deposition (LA-ALD) combined technology, the binding force of the coating and the titanium substrate is remarkably improved, high-energy particles are used for bombarding the surface of the titanium substrate in the low-temperature plasma treatment, residual impurities are effectively removed, the surface roughness and active sites are increased, and the surface hardness of the titanium substrate is improved. In the pulsed bias magnetron sputtering process, the surface of the substrate is further cleaned through periodic ion bombardment, atomic diffusion and mixing between the coating and the substrate are promoted, a transition layer structure is formed, and therefore the binding force is greatly enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode preparation, in particular to a method for preparing a novel mixed metal oxide coated titanium electrode. Background Art

[0002] Titanium electrodes play a key role in many fields such as the chlor-alkali industry, sewage treatment, and electrolytic metallurgy due to their good conductivity, corrosion resistance, and chemical stability. With the continuous improvement of industrial development requirements for electrode performance, in order to further improve the electrocatalytic performance of titanium electrodes, extend service life, and reduce costs, the preparation of mixed metal oxide coatings on the surface of titanium substrates has become an important research direction. Mixed metal oxide coatings can give electrodes specific electrochemical properties to meet the needs of different industrial scenarios. Therefore, the development of efficient and high-quality mixed metal oxide coated titanium electrode preparation technology is of great significance to promoting the development of related industries.

[0003] Currently, the common preparation methods of mixed metal oxide coated titanium electrodes have many shortcomings. The coatings prepared by thermal decomposition are prone to cracking and falling off, and the coating uniformity is poor, resulting in uneven distribution of active sites. The invention patent with publication number CN104988535A discloses a mixed metal oxide coated electrode and its preparation method, which uses a single thermal decomposition method to prepare the metal oxide coating. The coating uniformity is poor, and cracks and pores are easily formed on the surface of the titanium substrate, resulting in insufficient exposure of active sites and easy falling off. The deposited single oxide coating has a single catalytic activity and insufficient oxidation ability when facing complex pollutants. In addition, the sol-gel process is complex and the cost is high, which limits its large-scale application. The coating prepared by electroplating has poor uniformity, resulting in poor overall electrode performance. Although traditional atomic layer deposition technology can achieve precise control at the atomic level, the deposition rate is low and the industrial application efficiency is limited. The bottom layer prepared by traditional magnetron sputtering has limited bonding strength with the substrate, and the coating structure is not dense enough, which affects the long-term stability of the electrode and makes it difficult to meet the preparation requirements of high-performance electrodes. Summary of the Invention

[0004] The purpose of the present invention is to make up for the shortcomings of the existing technology and provide a novel method for preparing a mixed metal oxide coated titanium electrode. In the pretreatment stage of the titanium substrate, low-temperature plasma treatment technology is adopted to bombard the surface of the titanium substrate with high-energy particles in the plasma to remove residual organic impurities and increase the surface roughness and active sites. In the magnetron sputtering bottom layer process, the bias voltage applied to the titanium substrate is periodically changed to achieve precise control of the bottom layer structure and performance, and enhance the bonding force between the bottom layer and the substrate. In the process of laser-induced atomic layer deposition to grow a functional modified layer, a laser beam is introduced to irradiate the precursor molecules, which promotes the decomposition and surface reaction of the precursor, increases the deposition rate, improves the coating quality, and realizes precise control of the composition, structure and performance of the modified layer. Through this method, the bonding force between the coating and the titanium substrate, the density of the bottom layer and the deposition quality and rate of the modified layer are significantly improved, the surface properties of the coating are precisely controlled, and a mixed metal oxide coated titanium electrode with excellent electrocatalytic performance, high stability and long service life is prepared.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a novel mixed metal oxide coated titanium electrode, the method comprising the following specific steps: Titanium substrate pretreatment: The titanium plate is polished with 120-800 grit sandpaper in a gradient manner, and the polished titanium substrate is etched with hydrochloric acid solution, surface activated with argon plasma, and dried to obtain a clean substrate surface with appropriate roughness; Magnetron sputtering bottom layer: In an argon-oxygen mixed atmosphere, by sputtering a bismuth-cerium-cobalt alloy target and applying a pulsed bias, the deposition temperature is 150-300°C for 30-60 minutes to form a uniform and dense mixed metal oxide bottom layer; Laser deposition modification layer: At a temperature of 150-250°C, trimethylaluminum, tetrakis(dimethylamino)titanium and water precursors are alternately introduced, and laser irradiation is used to promote the reaction. 50-200 cycles of deposition are performed to form an ultra-thin composite modification layer. Post-treatment annealing: The titanium substrate deposited with the mixed metal oxide bottom layer and the functional modification layer is placed in a tube furnace under a nitrogen atmosphere and cooled to room temperature along with the furnace to obtain a novel mixed metal oxide coated titanium electrode.

[0006] Furthermore, in the titanium substrate pretreatment step, the polished titanium substrate is placed in a hydrochloric acid solution with a volume ratio of 1:3, soaked at 60-80°C for 30-60 minutes, taken out and rinsed with deionized water until neutral, and the cleaned titanium substrate is placed in a low-temperature plasma device, using argon as the working gas, a processing power of 50-100W, and a processing time of 5-10 minutes. The high-energy particles in the plasma bombard the surface of the titanium substrate to further clean the surface and remove residual organic impurities. The plasma-treated titanium substrate is dried at 100-120°C for 1-2 hours to obtain a titanium substrate base with a cleaned and activated surface.

[0007] Furthermore, in the magnetron sputtering bottom layer step, a bismuth-cerium-cobalt alloy target is sputtered and a pulse bias is applied. Specifically, the pretreated titanium substrate is placed in a magnetron sputtering device equipped with a pulse bias power supply, and bismuth, cerium, and cobalt metal targets with a purity of 99.9% are used. Argon is used as the sputtering gas and oxygen is used as the reaction gas to deposit a mixed metal oxide bottom layer on the surface of the titanium substrate. During the sputtering process, the sputtering power is 100-300W, the argon flow rate is 20-50sccm, the oxygen flow rate is 5-15sccm, the working pressure is 0.5-2Pa, the deposition time is 30-60 minutes, and the deposition temperature is 150-300°C.

[0008] Furthermore, in the magnetron sputtering bottom layer step, a bismuth-cerium-cobalt alloy target is sputtered and a pulse bias is applied, the sputtering power is 100-300W, a medium frequency power supply is used, the frequency is 40kHz, the argon flow rate is 20-50sccm, the oxygen flow rate is 5-15sccm, the working pressure is 0.5-2Pa, and the deposition temperature is controlled at 150-300°C by an infrared heating system, and the substrate temperature fluctuation is ≤±5°C.

[0009] Furthermore, in the magnetron sputtering bottom layer step, the deposition time is 30-60 minutes, the deposition rate is controlled at 15-30 nm / min, and finally a mixed metal oxide bottom layer with a thickness of 1-5 μm is formed. After the deposition is completed, the oxygen and argon gases are first turned off, and the vacuum pump is kept running for 30 minutes. The substrate is taken out after cooling to ≤80°C.

[0010] Furthermore, in the laser deposition modification layer step, the titanium substrate deposited with the mixed metal oxide bottom layer is transferred to an atomic layer deposition device equipped with a laser system, and an ultra-thin, uniform functional modification layer is grown on the surface of the bottom layer. Trimethylaluminum TMA, TDMAT, and water are used as precursors, and nitrogen is used as a carrier gas and purge gas. The process parameters of laser-induced atomic layer deposition LA-ALDde are: reaction temperature of 150-250°C, TMA pulse time of 0.1-0.5 seconds, purge time of 5-15 seconds, TDMAT pulse time of 0.1-0.5 seconds, purge time of 5-15 seconds, water pulse time of 0.05-0.2 seconds, purge time of 5-15 seconds.

[0011] Furthermore, in the laser deposition modification layer step, a laser beam is introduced to irradiate the precursor molecules, the laser wavelength is 248-355nm, the laser power is 10-50mJ / cm², the laser pulse frequency is 10-50Hz, the laser irradiation time is 0.1-1 second per cycle, the deposition cycle number is 50-200 cycles, and a functional modification layer with a thickness of 5-20nm is obtained.

[0012] Furthermore, in the post-treatment annealing step, the titanium substrate deposited with the mixed metal oxide bottom layer and the functional modification layer is placed in a tubular furnace, heated to 300-400°C at a heating rate of 5-10°C / min in a nitrogen atmosphere, kept warm for 1-2 hours, and then cooled to room temperature with the furnace to obtain a new mixed metal oxide coated titanium electrode.

[0013] Compared with the existing technology, this novel method for preparing a mixed metal oxide coated titanium electrode has the following beneficial effects: 1. The present invention significantly improves the bonding strength between the coating and the titanium substrate by combining low-temperature plasma treatment, pulsed bias magnetron sputtering and laser-induced atomic layer deposition (LA-ALD). The low-temperature plasma treatment uses high-energy particles to bombard the surface of the titanium substrate, effectively removing residual impurities and increasing surface roughness and active sites. During the pulsed bias magnetron sputtering process, periodic ion bombardment further cleans the substrate surface, promotes atomic diffusion and mixing between the coating and the substrate, and forms a transition layer structure, thereby greatly enhancing the bonding strength. The LA-ALD technology irradiates the precursor molecules with a laser beam, promoting their adsorption and reaction on the underlying surface, ensuring that the modified layer is tightly bonded to the underlying layer, and the coating is firmly bonded to the substrate, significantly improving the stability and service life of the electrode.

[0014] 2. The present invention optimizes the underlying structure through pulse bias magnetron sputtering technology, making it more dense and uniform, and reducing the porosity. The LA-ALD technology achieves precise control of the deposition process through laser induction, and can accurately regulate the composition, structure and performance of the modified layer. By adjusting the wavelength, power and irradiation time of the laser, specific precursor molecules or surface sites can be selectively excited to meet the needs of different electrochemical application scenarios. In addition, the functional modified layer can effectively protect the underlying mixed metal oxides and prevent them from dissolving, falling off, etc. during the electrochemical process, further improving the overall performance of the electrode, so that it can maintain efficient and stable catalytic activity under various electrolysis conditions.

[0015] Other advantages, objects and features of the present invention will be described in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be learned from the practice of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. Those skilled in the art can also derive other drawings based on these drawings without inventive effort.

[0017] Figure 1 This is a process flow chart of a preparation method for a novel mixed metal oxide coated titanium electrode; Figure 2 The figure is a flow chart of a novel method for preparing a mixed metal oxide coated titanium electrode. DETAILED DESCRIPTION

[0018] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined purpose of the invention, the specific implementation methods, structures, features and effects of the present invention are described in detail below in conjunction with the accompanying drawings and preferred embodiments.

[0019] Example 1 A pure titanium plate with a size of 10 cm × 10 cm × 0.5 cm was selected as the base material. Figure 1As shown, 120 mesh, 240 mesh, and 400 mesh sandpaper are used for polishing in sequence. The same direction is maintained during the polishing process, and each level of sandpaper is used to ensure that each area of ​​the titanium plate is evenly polished until the surface presents a uniform frosted texture. After polishing, the titanium plate is placed in a configured hydrochloric acid solution with a volume ratio of 1:3. The solution is placed in a corrosion-resistant glass container and placed in a constant temperature water bath at 60°C for 30 minutes. During this period, the container is gently shaken to make the etching more uniform. After the soaking is completed, the titanium plate is quickly removed and rinsed with a large amount of deionized water until the pH value of the rinsed water is neutral. Then, the titanium plate is placed in the reaction chamber of the low-temperature plasma equipment, with argon gas with a purity of 99.9% as the working gas, the processing power is set to 50W, and the treatment is carried out for 5 minutes. Under the action of plasma, the surface of the titanium plate is further cleaned and activated. Finally, the treated titanium plate is placed in a blast drying oven, the temperature is set to 100°C, and it is dried for 1 hour. After cooling to room temperature, it is taken out for use.

[0020] The pre-treated titanium plate was mounted on the sample stage of the magnetron sputtering equipment, ensuring that it was firmly mounted and in the right position directly below the target. The equipment used bismuth, cerium, and cobalt metal targets with a purity of 99.9%. The vacuum pump system of the equipment was turned on in sequence to evacuate the reaction chamber to a vacuum state. When the vacuum degree reached 5×10 -4 Pa, argon and oxygen are introduced, the argon flow rate is set to 20sccm, and the oxygen flow rate is 5sccm, so that the working pressure is stabilized at 0.5Pa, the sputtering power supply is turned on, the sputtering power is set to 100W, and the pulse bias power supply is turned on at the same time, the pulse frequency is set to 10kHz, the pulse width is 1μs, the bias amplitude is -50V, and the duty cycle is 10%. At a deposition temperature of 150°C, sputtering is continued for 45 minutes to deposit a mixed metal oxide bottom layer on the surface of the titanium plate. During the deposition process, it can be observed that the color of the titanium plate surface gradually changes, forming a uniform thin film.

[0021] The titanium plate with the bottom layer deposited was carefully transferred to the reaction chamber of the atomic layer deposition equipment equipped with a laser system to ensure that the bottom layer was not damaged during the transfer process. Trimethylaluminum (TMA), tetrakis(dimethylamino)titanium (TDMAT), and water were used as precursors. The reaction temperature was set to 150°C. The TMA precursor was first introduced with a pulse time of 0.1 seconds. Then nitrogen was introduced for purge with a purge time of 5 seconds. Then the laser system was turned on with a laser wavelength of 248 nm and a laser power of 10 mJ / cm 2 The laser pulse frequency is 10 Hz, and the laser irradiation time is 0.1 second per cycle, so that TMA can be better adsorbed and reacted under the action of the laser. Then a water pulse is introduced for 0.05 seconds, followed by a 5-second nitrogen purge and laser irradiation. After that, a TDMAT pulse is introduced for 0.1 seconds, a 5-second nitrogen purge and laser irradiation. This cycle is repeated 50 times to grow a functional modification layer on the surface of the bottom layer.

[0022] The deposited electrode was placed in a high-temperature resistant alumina boat and carefully placed in a tubular furnace. Nitrogen with a purity of 99.9% was introduced as a protective atmosphere. The gas flow rate was set to 500 sccm and slowly heated to 300°C at a heating rate of 5°C / min. After reaching the temperature, it was kept warm for 1 hour to allow the electrode to fully adjust its structure and optimize its performance at high temperature. After the insulation was completed, the heating power was turned off, and nitrogen was continuously introduced. The electrode was allowed to cool naturally to room temperature with the furnace, and finally a new mixed metal oxide coated titanium electrode was obtained.

[0023] After observation and testing, its surface coating is tightly bonded to the titanium substrate. When tested with a professional coating adhesion test tool, no coating peeling phenomenon was found. In the simulation of actual electrochemical reaction experiments, the electrode exhibited good catalytic activity and was able to quickly promote the reaction. During long-term continuous use, the electrode performance was stable, and there was no performance degradation due to external environmental factors such as temperature and humidity changes. The service life was effectively extended. In multiple repeated experiments, it was able to maintain a stable working state, with good reliability and consistency.

[0024] Example 2 Select an industrial pure titanium plate with a specification of 15cm×15cm×0.8cm, first use 120-mesh sandpaper for preliminary polishing to remove obvious oxide scale and impurities on the surface, then use 240-mesh, 400-mesh, and 600-mesh sandpaper for fine polishing in sequence, with uniform force during polishing to ensure that the surface of the titanium plate is flat and the roughness is consistent. After polishing, place the titanium plate in a special corrosion-resistant plastic container, pour in a hydrochloric acid solution with a volume ratio of 1:3, place the container in a constant temperature water bath at 70°C, let the titanium plate soak in the solution for 45 minutes, and gently stir the solution every 10 minutes during the period to make the etching effect more uniform. After soaking, immediately Rinse the titanium plate with a large amount of deionized water, repeatedly rinse for more than 5 times until the pH test paper of the rinse water shows neutral. Then, place the titanium plate in the reaction chamber of the low-temperature plasma treatment equipment, introduce argon gas with a purity of 99.9%, set the treatment power to 75W, and the treatment time to 7.5 minutes to allow the plasma to fully act on the surface of the titanium plate to increase the surface activity. Finally, place the treated titanium plate in a hot air circulation drying oven, adjust the temperature to 110°C, and dry it for 1.5 hours. During the drying process, the hot air circulation frequency in the box is set to once every 10 minutes to ensure that the titanium plate is thoroughly dried. After taking it out, place it in a dust-free environment to cool for use.

[0025] The cooled titanium plate was mounted on the rotatable sample holder of the magnetron sputtering equipment. The position of the sample holder was adjusted to keep the distance between the titanium plate and the bismuth, cerium, and cobalt metal targets (all with a purity of 99.9%) at 8 cm. The vacuum system of the equipment was started. When the vacuum degree of the reaction chamber reached 5×10 -4Pa, start to introduce argon and oxygen, the argon flow rate is set to 35sccm, the oxygen flow rate is 10sccm, and the gas flow rate is adjusted to stabilize the working pressure at 1Pa. Turn on the sputtering power supply, set the sputtering power to 200W, and turn on the pulse bias power supply at the same time, set the pulse frequency to 50kHz, the pulse width to 5μs, the bias amplitude to -150V, and the duty cycle to 45%. At a deposition temperature of 225°C, let the equipment work continuously for 45 minutes. During the sputtering process, the sample holder rotates at a constant speed of 8 revolutions per minute to ensure that the mixed metal oxide bottom layer is evenly deposited on the surface of the titanium plate. It can be seen that the surface of the titanium plate is gradually covered with a layer of gray-black film.

[0026] The titanium plate with the deposited bottom layer was carefully transferred to the reaction chamber of the laser-induced atomic layer deposition equipment and fixed in position. Trimethylaluminum (TMA), tetrakis(dimethylamino)titanium (TDMAT) and deionized water were used as precursors. The reaction temperature was set to 200℃. The TMA precursor was first introduced with a pulse time of 0.3 seconds, followed by a 10-second purge operation with nitrogen to remove excess precursor. The laser system was then turned on, using a laser with a wavelength of 308nm, a laser power of 30mJ / cm², a laser pulse frequency of 30Hz, and an irradiation time of 0.5 seconds per cycle to induce TMA to react on the bottom surface of the titanium plate. Then, a water pulse was introduced for 0.1 seconds, followed by a 10-second nitrogen purge and laser irradiation. After that, a TDMAT pulse was introduced for 0.3 seconds, and a 10-second nitrogen purge and laser irradiation were also performed. This cycle was repeated for 125 times, resulting in the growth of a uniform and dense aluminum oxide-titanium dioxide composite modification layer on the bottom surface. At this time, the surface of the titanium plate exhibited a uniform silver-white luster.

[0027] The coated titanium electrode was placed in a crucible made of high-purity alumina, and the crucible was placed in the constant temperature zone of a tube furnace. Nitrogen with a purity of 99.9% was introduced as a protective gas. The gas flow rate was controlled at 800 sccm, and the temperature of the tube furnace was raised from room temperature to 350°C at a heating rate of 7.5°C / min. After reaching the target temperature, the electrode was kept warm in the furnace for 1.5 hours to further optimize the internal structure of the coating. After the insulation was completed, the heating power was turned off, and nitrogen was continued to be introduced to allow the electrode to slowly cool to room temperature in the furnace. The entire cooling process took about 5 hours, and finally a new type of mixed metal oxide coated titanium electrode with excellent performance was obtained.

[0028] After professional testing, its surface coating is evenly covered without any defects such as holes and cracks, and is firmly bonded to the titanium substrate. During the bending test, the coating did not peel or fall off. In specific electrochemical reaction application scenarios, the electrode has a significant catalytic effect on the reaction, which can effectively reduce the activation energy of the reaction and enable the reaction to proceed quickly at a lower voltage. At the same time, the electrode exhibits excellent stability. Even after working for a long time in environments with different pH and temperature fluctuations, its electrocatalytic performance remains stable without obvious attenuation, which greatly reduces the frequency of electrode replacement.

[0029] Example 3 Take a titanium plate with the size of 20cm×20cm×1cm, such as Figure 2 As shown, the surface was coarsely ground with 120-mesh sandpaper to remove thick oxide layers and impurities, and then finely ground with 240-mesh, 400-mesh, 600-mesh, and 800-mesh sandpapers. During the grinding process, the titanium plate was rinsed with clean water to prevent the debris generated by the sandpaper from scratching the surface of the titanium plate. The titanium plate was polished until the surface was smooth and had a uniform metallic luster. The polished titanium plate was placed in a solution prepared by analytical pure hydrochloric acid and deionized water in a volume ratio of 1:3, and immersed in a constant temperature water bath at 80°C for 60 minutes. A magnetic field was used during the soaking process. The solution was stirred at a low speed with a force stirrer to make the etching more complete. After the immersion was completed, the titanium plate was quickly taken out and repeatedly rinsed with a large amount of deionized water until the rinsed water was tested to be neutral with a pH test paper. Subsequently, the titanium plate was placed in a low-temperature plasma treatment device, high-purity argon gas was introduced, the processing power was set to 100W, the processing time was 10 minutes, and the surface of the titanium plate was activated. Finally, the titanium plate was placed in a drying oven and dried at 120°C for 2 hours. After the drying was completed, the titanium plate was placed in a clean drying dish and cooled to room temperature for use.

[0030] The cooled titanium plate was mounted on the sample stage of the magnetron sputtering equipment to ensure that it was firmly mounted and positioned accurately. The equipment used bismuth, cerium, and cobalt metal targets (all with a purity of 99.9%). The vacuum system of the equipment was started and the reaction chamber was evacuated to 5×10⁻. 4 Pa, introduce argon and oxygen, set the argon flow rate to 50sccm, and the oxygen flow rate to 15sccm. Adjust the gas flow rate to stabilize the working pressure at 2Pa, turn on the sputtering power supply, adjust the sputtering power to 300W, and turn on the pulse bias power supply at the same time, set the pulse frequency to 100kHz, the pulse width to 10μs, the bias amplitude to -300V, and the duty cycle to 80%. At a deposition temperature of 300°C, perform magnetron sputtering deposition for 60 minutes. During the deposition process, the sample stage rotates at a speed of 10 rpm to uniformly deposit the mixed metal oxide bottom layer on the surface of the titanium plate.

[0031] The titanium plate with the bottom layer deposited was transferred to an atomic layer deposition device equipped with a laser system. Trimethylaluminum (TMA), tetrakis(dimethylamino)titanium (TDMAT), and water were used as precursors. The reaction temperature was set to 250°C. TMA was first introduced with a pulse time of 0.5 seconds, followed by a 15-second purge with nitrogen. The laser was then turned on with a wavelength of 355nm, a laser power of 50mJ / cm², a laser pulse frequency of 50Hz, and an irradiation time of 1 second per cycle to promote a full reaction between TMA and the bottom surface of the titanium plate. Subsequently, a water pulse was introduced for 0.2 seconds, followed by a 15-second nitrogen purge and laser irradiation. After that, a TDMAT pulse was introduced for 0.5 seconds, followed by a 15-second nitrogen purge and laser irradiation. This process was repeated for 200 cycles to grow a functional modification layer of appropriate thickness on the bottom surface.

[0032] The titanium electrode with completed coating deposition was placed in a high-temperature resistant quartz boat, and the quartz boat was placed in a tube furnace. High-purity nitrogen was introduced as a protective gas with a gas flow rate of 1000 sccm. The temperature of the tube furnace was raised from room temperature to 400°C at a heating rate of 10°C / min. After reaching the temperature, it was kept warm for 2 hours to further optimize the structure and performance of the coating. After the insulation was completed, the heating power was turned off, and nitrogen was continuously introduced to allow the electrode to cool naturally to room temperature with the furnace, and finally a new mixed metal oxide coated titanium electrode was obtained.

[0033] After inspection, its surface coating is complete and dense, and is firmly bonded to the titanium substrate. After undergoing severe vibration and a certain degree of mechanical friction, the coating remains intact. In actual electrochemical applications, the electrode exhibits good catalytic ability for a variety of electrochemical reactions, which can significantly accelerate the reaction rate and improve the reaction efficiency. Moreover, the electrode has excellent corrosion resistance and can work for a long time in harsh environments such as strong acids and strong alkalis with minimal performance fluctuations, always maintaining a stable working state, effectively improving the scope of application and service life of the electrode.

[0034] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as above in terms of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art can, without departing from the scope of the technical solution of the present invention, make some changes or modifications to equivalent embodiments using the technical contents disclosed above. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A novel method for preparing a mixed metal oxide coated titanium electrode, characterized in that: The method comprises the following specific steps: Titanium substrate pretreatment: The titanium plate is polished with 120-800 grit sandpaper in a gradient manner, and the polished titanium substrate is etched with hydrochloric acid solution, surface activated with argon plasma, and dried to obtain a clean substrate surface with appropriate roughness; Magnetron sputtering bottom layer: In an argon-oxygen mixed atmosphere, by sputtering a bismuth-cerium-cobalt alloy target and applying a pulsed bias, the deposition temperature is 150-300°C for 30-60 minutes to form a uniform and dense mixed metal oxide bottom layer; Laser deposition modification layer: At a temperature of 150-250°C, trimethylaluminum, tetrakis(dimethylamino)titanium and water precursors are alternately introduced, and laser irradiation is used to promote the reaction. 50-200 cycles of deposition are performed to form an ultra-thin composite modification layer. Post-treatment annealing: The titanium substrate deposited with the mixed metal oxide bottom layer and the functional modification layer is placed in a tube furnace under a nitrogen atmosphere and cooled to room temperature along with the furnace to obtain a novel mixed metal oxide coated titanium electrode.

2. The method for preparing a novel mixed metal oxide coated titanium electrode according to claim 1, characterized in that: In the titanium substrate pretreatment step, the polished titanium substrate is placed in a hydrochloric acid solution with a volume ratio of 1:3, soaked at 60-80°C for 30-60 minutes, taken out and rinsed with deionized water until neutral, and the cleaned titanium substrate is placed in a low-temperature plasma device, using argon as the working gas, a processing power of 50-100W, and a processing time of 5-10 minutes. The high-energy particles in the plasma bombard the surface of the titanium substrate to further clean the surface and remove residual organic impurities. The plasma-treated titanium substrate is dried at 100-120°C for 1-2 hours to obtain a titanium substrate base with a cleaned and activated surface.

3. The method for preparing a novel mixed metal oxide coated titanium electrode according to claim 1, characterized in that: In the magnetron sputtering bottom layer step, a bismuth-cerium-cobalt alloy target is sputtered and a pulse bias is applied. Specifically, the pretreated titanium substrate is placed in a magnetron sputtering device equipped with a pulse bias power supply, and bismuth, cerium, and cobalt metal targets with a purity of 99.9% are used. Argon is used as the sputtering gas and oxygen is used as the reaction gas to deposit a mixed metal oxide bottom layer on the surface of the titanium substrate. During the sputtering process, the sputtering power is 100-300W, the argon flow rate is 20-50sccm, the oxygen flow rate is 5-15sccm, the working pressure is 0.5-2Pa, the deposition time is 30-60 minutes, and the deposition temperature is 150-300°C.

4. The method for preparing a novel mixed metal oxide coated titanium electrode according to claim 1, characterized in that: In the magnetron sputtering bottom layer step, a bismuth-cerium-cobalt alloy target is sputtered and a pulse bias is applied. The sputtering power is 100-300W, a medium frequency power supply is used, the frequency is 40kHz, the argon flow rate is 20-50sccm, the oxygen flow rate is 5-15sccm, the working pressure is 0.5-2Pa, and the deposition temperature is controlled at 150-300°C by an infrared heating system. The substrate temperature fluctuation is ≤±5°C.

5. The method for preparing a novel mixed metal oxide coated titanium electrode according to claim 1, characterized in that: In the magnetron sputtering bottom layer step, the deposition time is 30-60 minutes, the deposition rate is controlled at 15-30 nm / min, and finally a mixed metal oxide bottom layer with a thickness of 1-5 μm is formed. After the deposition is completed, the oxygen and argon gases are first turned off, and the vacuum pump is kept running for 30 minutes. The substrate is taken out after cooling to ≤80°C.

6. The method for preparing a novel mixed metal oxide coated titanium electrode according to claim 1, characterized in that: In the laser deposition modification layer step, the titanium substrate deposited with the mixed metal oxide bottom layer is transferred to an atomic layer deposition device equipped with a laser system, and an ultra-thin, uniform functional modification layer is grown on the surface of the bottom layer. Trimethylaluminum (TMA), TDMAT, and water are used as precursors, and nitrogen is used as a carrier gas and a purge gas. The laser-induced atomic layer deposition (LA-ALD) process parameters are as follows: reaction temperature of 150-250°C, TMA pulse time of 0.1-0.5 seconds, purge time of 5-15 seconds, TDMAT pulse time of 0.1-0.5 seconds, purge time of 5-15 seconds, water pulse time of 0.05-0.2 seconds, purge time of 5-15 seconds.

7. The method for preparing a novel mixed metal oxide coated titanium electrode according to claim 1, characterized in that: In the laser deposition modification layer step, a laser beam is introduced to irradiate the precursor molecules. The laser wavelength is 248-355 nm, the laser power is 10-50 mJ / cm², the laser pulse frequency is 10-50 Hz, the laser irradiation time is 0.1-1 second per cycle, and the deposition cycle number is 50-200 cycles, thereby obtaining a functional modification layer with a thickness of 5-20 nm.

8. The method for preparing a novel mixed metal oxide coated titanium electrode according to claim 1, characterized in that: In the post-treatment annealing step, the titanium substrate deposited with the mixed metal oxide bottom layer and the functional modification layer is placed in a tubular furnace, heated to 300-400°C at a heating rate of 5-10°C / min in a nitrogen atmosphere, kept warm for 1-2 hours, and then cooled to room temperature in the furnace to obtain a novel mixed metal oxide coated titanium electrode.

Citation Information

Patent Citations

  • Mixed metal oxide coating electrode and preparation method thereof

    CN104988535A

Cited By

  • Preparation method of anode with MnO2 / IrO2 coating

    CN122105492A

  • A method for preparing an anode with a MnO2 / IrO2 coating

    CN122105492B